2020
DOI: 10.3390/biom10091239
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Segment of TvCyP2 Cyclophilin from Trichomonas vaginalis Is Involved in Self-Association, Membrane Interaction, and Subcellular Localization

Abstract: In Trichomonas vaginalis (T. vaginalis), cyclophilins play a vital role in dislodging Myb proteins from the membrane compartment and leading them to nuclear translocation. We previously reported that TvCyP1 cyclophilin from T. vaginalis forms a dimer and plays an essential role in moving the Myb1 transcription factor toward the nucleus. In comparison, TvCyP2 containing an extended segment at the N-terminus (N-terminal segment) formed a monomer and showed a different role in regulating protein trafficking. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
(91 reference statements)
1
5
0
Order By: Relevance
“…In comparison, r Tv CyP2 was prepared and analyzed using method 3. UV-LC–MS 2 data indicated that r Tv CyP2 also contains a high thiol percentage (Table S4), consistent with the reported structure . However, as shown in Figure D, one disulfide cluster, Cy2T1–Cy2T3, was detected with insignificant control–target mispairings.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In comparison, r Tv CyP2 was prepared and analyzed using method 3. UV-LC–MS 2 data indicated that r Tv CyP2 also contains a high thiol percentage (Table S4), consistent with the reported structure . However, as shown in Figure D, one disulfide cluster, Cy2T1–Cy2T3, was detected with insignificant control–target mispairings.…”
Section: Resultssupporting
confidence: 86%
“…UV-LC−MS 2 data indicated that rTvCyP2 also contains a high thiol percentage (Table S4), consistent with the reported structure. 35 However, as shown in Figure 4D, one disulfide cluster, Cy2T1−Cy2T3, was detected with insignificant control−target mispairings. More importantly, the identified C53−C181 disulfide contained in Cy2T1−Cy2T3 of rTvCyP2 (Figure S13) is conserved in rTvCyP1 which exists as C41−C169 in disulfide pattern 1 (C41−C169/C164−C153 and C135 free) of rTvCyP1.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In particular, the sequence comparison of TgCyp23 with human CypA suggested that, among the 13 residues characterizing the CsA-binding pocket in the human CypA–CsA complex (Arg55, Phe60, Met61, Gln63, Gly72, Ala101, Asn102, Ala103, Gln111, Phe113, Trp121, Leu122, His126), 12 are identical in TgCyp23, including a single tryptophan that is likely to be critical for CsA binding. However, TgCyp23 possesses a 40-residue N-terminal extension relative to human CypA (Figure ) that might be involved in the membrane interaction and subcellular localization in agreement to other parasitic systems . On the other hand, TgCyp18.4 contains some striking amino acid substitutions in the active site (e.g., Met61, Trp121, and His126 of CypA are replaced by Ala50, His111, and Tyr116, respectively, in TgCyp18.4), which could, in principle, influence the catalytic properties of the enzyme and its affinity for CsA, making it an attractive candidate for the design of new CsA derivative compounds (Figure ).…”
Section: Resultsmentioning
confidence: 79%
“…However, TgCyp23 possesses a 40-residue N-terminal extension relative to human CypA ( Figure 1 ) that might be involved in the membrane interaction and subcellular localization in agreement to other parasitic systems. 32 On the other hand, TgCyp18.4 contains some striking amino acid substitutions in the active site (e.g., Met61, Trp121, and His126 of CypA are replaced by Ala50, His111, and Tyr116, respectively, in TgCyp18.4), which could, in principle, influence the catalytic properties of the enzyme and its affinity for CsA, making it an attractive candidate for the design of new CsA derivative compounds ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%